Classical Associations and Societies in the United Kingdom - Sparkes, Brian A. (Hyperboreus, 2014)
The paper gives an overview of Classical scholarly societies and associations, for the most part not state-funded, which were founded in the United Kingdom in the 19th and the 20th centuries. It outlines their speciﬁc peculiarities, tasks, publications, problems and perspectives.